Estimation of yield and nitrogen use efficiencies in hybrid maize varieties through site specific nitrogen management based on leaf color chart (LCC) - Suhail Fayaz; Raihana Habib Kanth; Tauseef A. Bhat; Eajaz Ahmad Dar; Zahoor Ahmad Shah; Moneesa Bashir; Aijaz Nazir; Bilkees Jamsheed; Mohd. Salim Mir; Zahoor A. Dar; Shailja Sharma; Aabid Hussain Lone; et al. (Scientific Reports)
Abstract Exorbitant praxis of nitrogen pioneered and opened up the usage of time-specific and need-based nitrogen management. The leaf color chart (LCC), being one of the handy tool, is put to use for the estimation of the indirect leaf N, and also heightens the competence of crop N administration. Integrating leaf color chart assessments into maize cultivation practices can provide a practical and cost-effective approach for tailoring nitrogen applications, leading to improved resource-use efficiency and sustainable maize production. To perceive the specific leaf color chart (LCC) value for precision maneuvering of nitrogen in different maize hybrids, a field experiment was carried out at the research farm of Division of Agronomy, FoA, Wadura, Sopore, SKUAST-Kashmir, in the years 2019 and 2020 (Kharif seasons). Split Plot Design (SPD) employing three maize varieties (Shalimar Maize Hybrid-2 (SMH-2), Kanchan-517 and Vivek-45) in main plots and precision management of nitrogen (T1: Control, T2: Recommended Nitrogen (120 kg N ha–1), T3: 25% N as basal LCC @20 (≤ 3) kg N ha−1, T4: 25% N as basal LCC @30 (≤ 3) kg N ha−1, T5: 25% N as basal LCC @20 (≤ 4) kg N ha−1, T6: 25% N as basal LCC @30 (≤ 4) kg N ha−1, T7: 25% N as basal LCC @20 (≤ 5) kg N ha−1 and T8: 25% N as basal LCC @30 (≤ 5) kg N ha−1) in sub-plots was systemized. The pooled means indicated that SMH-2 chalked up utmost values in growth (plant height 189.4 cm) and periodic leaf area index and yield parameters with a grain yield of 6.1 t ha–1, straw yield of 10.6 t ha–1, respectively. The LCC value of @ 30 (≤ 5) kg N ha–1 set down statistically highest and significant grain (6.0 t ha–1) and straw yield (10.8 t ha–1) pooled over the years amidst other nitrogen management treatments, respectively. LCC @ 20 (≤ 5) kg N ha–1 turned up to have highest apparent N recovery (REN) followed by LCC @ 30 (≤ 5) kg N ha-1 whereas LCC @ 20 (≤ 4) kg N ha–1 which was at par with LCC @ 20 (≤ 5) kg N ha-1 recorded maximum agronomic efficiency (AE). LCC @ 20 (≤ 3) kg N ha–1 showed the highest physiological efficiency (PE) and partial factor productivity (Pfp). Furthermore, different rice genotypes manifested significant effects vis-à-vis Pfp and REN, which were maximum in SMH-2 contrasted with Kanchan-517 and Vivek-45. In the interim, the economics of pooled data divulged that the maximum B: C ratio was observed in SMH-2 and LCC @ 30 (≤ 5) kg N ha–1. Therefore, site-specific nutrient management through LCC proved to be an effective strategy to maximize yield and nitrogen use efficiency in hybrid maize.